2018
DOI: 10.1021/acs.biomac.7b01648
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Order Release of Gossypol Improves Its Antifertility Effect and Reduces Its Side Effects Simultaneously

Abstract: Gossypol was considered a promising male contraceptive but finally failed due to two side effects: hypokalemia and the irreversibility of its contraceptive effect. Here we demonstrate that sustained zero-order release could be a solution for these problems. The in vitro release of gossypol from gossypol/PEG layer-by-layer films follows a perfect zero-order kinetics. In vivo tests indicate that the films can maintain the plasma drug concentration constant in male SD rats for ∼20 days for a 30-bilayer film. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…As a result, the film absorbance increased with increasing dipping cycles, as shown in Figure 2A. Similar to other hydrogen-bonded LBL films reported previously, [25][26][27] the PEG-LEU/TA film showed an exponential growth pattern ( Figure 2B). Moreover, the thickness of the LBL films increased following the same pattern ( Figure 2C).…”
Section: Preparation Of the Filmssupporting
confidence: 86%
See 1 more Smart Citation
“…As a result, the film absorbance increased with increasing dipping cycles, as shown in Figure 2A. Similar to other hydrogen-bonded LBL films reported previously, [25][26][27] the PEG-LEU/TA film showed an exponential growth pattern ( Figure 2B). Moreover, the thickness of the LBL films increased following the same pattern ( Figure 2C).…”
Section: Preparation Of the Filmssupporting
confidence: 86%
“…[21][22][23] When these films are fabricated from monodisperse polymers, zero-order release can be achieved. [24][25][26][27][28][29] Using this principle, dynamic LBL films of PEGylated leuprolide (PEG-LEU) and tannic acid (TA) were fabricated using dynamic hydrogen bonding as the driving force. Both in vitro and in vivo tests revealed that drug release from the film followed perfect zero-order kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] A particularly challenging delivery mode is zero-order, in which the dose of the delivered drug is independent of time or residual concentration in the delivery vehicle. 4,[13][14][15] In general, zero-order release systems are technologically more difficult to create and therefore result in significantly higher prices. 16 Sophisticated examples of spherical drug vehicles like porous microspheres or polymer micelles have both proven to be capable of ensuring zero-or near zero-release behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Gossypol is a natural product derived from the genus Gossypium , which is a phenolic aldehyde and acts as an inhibitor of various dehydrogenase enzymes [14]. Besides its putative contraceptive function, gossypol is a well-known antimalarial and a potential anticancer drug [15]. Recently, Saleh et al reported the critical role of gossypol in cell inflammation and oxidative stress [16].…”
Section: Introductionmentioning
confidence: 99%